Cahaya Ramadan and Youth Agency in Religious Institutions: A Participatory Action Research Study in Beranang, Malaysia - Iwanda Lubis, Muya Syaroh; Farid Alfadil; M Dzaky Virza Yahya; Abdillah Syafiq; Fatur Rahman; Dykhi Fernandez (ASSUNNAH PRESS, 2025)
Youth disengagement from religious institutions has become a growing concern in Muslim-majority societies, including Malaysia, where youth participation in mosque-based activities remains low despite strong state support. This participatory action research (PAR) study, conducted during Ramadan 1446 H (March 2–17, 2025) in Beranang, Selangor, examined the structural causes of youth disengagement and the transformative potential of authentic PAR that positions youth as co-researchers. Through four iterative PAR cycles involving 15 youth co-researchers and approximately 50 community youth, the study found that low participation is driven not by apathy but by structural barriers, including exclusion from decision-making, misalignment between religious discourse and contemporary realities, limited spaces for youth agency, and weak institutional management. The PAR process reshaped power relations across visible, hidden, and invisible dimensions, increasing participation from 1–2% to 7.6% and enabling 80% of co-researchers to assume leadership roles. Youth articulated meaningful spirituality through four interconnected dimensions—relevance, participation, community, and authenticity—challenging dominant prescriptive approaches. The establishment of a Youth Committee with formal decision-making authority, institutionalized through a Memorandum of Understanding with the mosque’s governing body, reflects a lasting structural transformation. This study argues that sustainable youth engagement in religious institutions requires redistributing power and redefining intergenerational relations rather than merely expanding youth programs.